PENERAPAN STRATEGI PEMBELAJARAN READING ALOUD DALAM MENINGKATKAN KEMAMPUAN MEMBACA SURAH PENDEK PILIHAN PELAJARAN PAI KELAS VA SD NEGERI 2 SRIBHAWONO KECAMATAN BANDAR SRIBHAWONO - kin, shodikin; Purwanti, Elly (Jurnal Pengembangan Profesi Guru (JPPG), 2024)
Abstract The purpose of this study was to improve the ability to read selected short surahs in PAI lessons for Class VA students at SD Negeri 2 Sribhawono. And to increase the effectiveness of the implementation of PAI learning in Class VA students at SD Negeri 2 Sribhawono. The writer's problem in this study can be formulated as follows: Can the application of the Reading Aloud Strategy improve the ability to read selected short surahs in Class VA students at SD Negeri 2 Sribhawono? This research is Classroom Action Research (CAR), where the teacher plays a direct role in the learning process. The subjects in this study were Class VA students at SD Negeri 2 Sribhawono, while the objects were the Reading Aloud Strategy and students' ability to read selected short surahs in the subject of Islamic Religion. Meanwhile, the sample for this study was all VA Class students for the 2023/2024 school year, which consisted of 22 students. Collecting data in this study used an evaluation test, namely before the action and after the action at each meeting and gave a score to each student. From the field data it is known that the ability to read short surahs chosen by students before the action is still relatively poor with an average acquisition of 58.47 in the 50-59 interval. Then the ability to read the short sura of the students' choice increased after the class action was carried out with an average acquisition of 82.01 in the good group at intervals of 76-100.